The factors that influence job satisfaction among employees in the organization / Siti Fatimah Nurfaten Zulkifli - Zulkifli, Siti Fatimah Nurfaten (2014)
This study aims to examme the factors that influence job satisfaction among employee in government sector. Specifically, focus on Selangor State Development Corporation (PKNS) as the respondents. It seeks to focus on factors influence job satisfaction such as supervision, interpersonal relationship, and working condition as predictors of job satisfaction.The sample of the study consisted of 102 employees in the organization. A questionnaire was used for data collection. The questionnaires consist of 29 questions divided in three sections. Section A, focus on factors influence job satisfaction. Section B, focus on job satisfaction. While, demographic factor of respondent focused in section C. 102 questionnaires were received back after 130 questionnaires were distributed to the respondents and the data used for analysis. The total respond rate realized was only 78.5 percent.